A Thermodynamically Favored Crystal Orientation in Mixed Formamidinium/Methylammonium Perovskite for Efficient Solar Cells. Issue 24 (22nd April 2019) - Xu, Ziqi; Liu, Zonghao; Li, Nengxu; Tang, Gang; Zheng, Guanhaojie; Zhu, Cheng; Chen, Yihua; Wang, Ligang; Huang, Yuan; Li, Liang; Zhou, Ning; Hong, Jiawang; et al.
Abstract: Crystal orientation has a great impact on the properties of perovskite films and the resultant device performance. Up to now, the exquisite control of crystal orientation (the preferred crystallographic planes and the crystal stacking mode with respect to the particular planes) in mixed‐cation perovskites has received limited success, and the underlying mechanism that governs device performance is still not clear. Here, a thermodynamically favored crystal orientation in formamidinium/methylammonium (FA/MA) mixed‐cation perovskites is finely tuned by composition engineering. Density functional theory calculations reveal that the FA/MA ratio affects the surface energy of the mixed perovskites, leading to the variation of preferential orientation consequently. The preferable growth along the (001) crystal plane, when lying parallel to the substrates, affects their charge transportation and collection properties. Under the optimized condition, the mixed‐cation perovskite (FA1– x MA x PbI2.87 Br0.13 (Cl)) solar cells deliver a champion power conversion efficiency over 21%, with a certified efficiency of 20.50 ± 0.50%. The present work not only provides a vital step in understanding the intrinsic properties of mixed‐cation perovskites but also lays the foundation for further investigation and application in perovskite optoelectronics. Abstract : A thermodynamically favored crystal preferable orientation growth along the (001) crystal plane is explored in formamidinium/methylammonium mixed perovskites, and the origin is found to be the reduction of surface energy. Combined with the (001) plane lying parallel to the substrate, it affects the charge transportation and collection in the resultant perovskite solar cells, resulting in a power conversion efficiency of 21.2%.